MORAL VALUES FOUND IN THE NOVEL ENTITLED “EVERYTHING I NEVER TOLD YOU” BY CELESTE NG - Diana Ariani; Rusman Roni; Mulyadi Mulyadi (ELTE Journal (English Languange Teaching and Education), 2020)
The purpose of this study is to find out what moral values are found in the novel ‘Everything I Never Told You’ by Celeste Ng. The researcher investigates moral values through novels because today the moral crisis among youths tends to increase. The data analysis technique in this study is a qualitative data analysis technique. The result of the study is the researcher found seven moral values in the novel namely honesty, loyalty, obedience, love and affection, independence, responsibility, and persistence.